A study on birth preparedness and complication readiness in the field practice area of RHTC of a tertiary care establishment in Central India - Banerjee, Maj Indrayudh; Arora, Vinod; Banerjee, Suchandra; Madhwani, Kishore P.; Singh, Jitendra K.; Sahasrabuddhe, Aarti (International Journal of Research in Medical Sciences, 2023)
Background: Every pregnant woman faces the risk of sudden, unpredictable complications that could end in death or injury to herself or to her infant. Birth preparedness and complication readiness is a strategy that encourages pregnant women, their families, and communities to effectively plan for births and deal with emergencies, if they occur. Objectives were to study the Knowledge of Birth Preparedness & Complication Readiness among the study subjects in the field practice area of RHTC of a tertiary care establishment in Central India. Methods: This cross-sectional study was carried out from January 2016 to June 2017 in the field practice area of RHTC of a tertiary care establishment in Central India. In the study d 420 women were included as per criteria. Data was recorded in the predesigned and pre tested proforma and were analysed by using SPSS V.20 software. Results: Out of the total 420 mothers, 75% belonged to the age group 20-25 years. Maximum study subjects (33.1%) belonged to General Category while 23.1% of mothers were Schedule Caste. Maximum mothers (70%) were homemakers, the rest were occupied in various capacities. The BPCR index overall was 49.86, with 85% institutional deliveries; ANC visits initiation at 68%. General awareness shows certain gaps which needs attention of health care workers. Conclusions: Lack of awareness about possible complications during the time of pregnancy, that of time of delivery or post-natal period was observed while interviewing the mothers.